Improving Products by Combining Usability and Emotions - Buker, Tina; Miehling, Jörg; Wartzack, Sandro (Design Methodology for Future Products, 2022)
User-friendly and successful products usually emerge when pure functionality meets good usability as well as an emotional and aesthetic design. Modern theoretical approaches consider all of those three aspects as equally important. In practice, however, they are often still treated independently from one another. Thus, neither positive nor negative interdependencies can be taken into account. This chapter tries to close this gap by examining the relationship of usability and emotions and introducing the idea of dual user integration that aims for combining both aspects. A concrete approach to balance both aspects focusing on emotional impressions and physical capacities of the user is presented to make dual user integration applicable. This proactive approach is called Application for Computer-Aided Design of Emotional impressions and Physical capacities (ACADE+P) and consists of three main steps: (1) user/product description, (2) product evaluation and (3) data-based derivation of quantitative recommendations for design improvements. In addition to the general framework, the specific workflow of the method including an analysis and synthesis phase is explained in detail.<br